Assessing the influence of pig slurry pH on the degradation of selected antibiotic compounds. (March 2022) - Nightingale, John; Carter, Laura; Sinclair, Chris J.; Rooney, Phil; Dickinson, Michael; Tarbin, Jonathan; Kay, Paul
Abstract: Veterinary medicines are routinely used in animal husbandry and the environment may consequently be exposed to them via manure applications. This presents potential environmental and societal risks such as toxicological effects to aquatic/terrestrial organisms and the spread of antimicrobial resistance. Regulatory studies that assess the degradability of veterinary antibiotics during manure storage currently permit the use of just one manure per animal type although we speculate that heterogenic properties such as pH could be driving significant variability within degradation rates. To bridge this knowledge gap and assess degradation variability with pH, laboratory degradation studies were performed on a broad range of antibiotics (ceftiofur, florfenicol, oxytetracycline, sulfamethoxazole and tylosin) at three different environmentally relevant pH levels (5.5, 7, and 8.5). The effect of pig slurry pH on degradation rates was found to be significant and compound specific. Usually, acidic slurries were found to inhibit degradation when compared to neutral pH, for florfenicol, tylosin, and ceftiofur; the associated changes in DT50 (half-life) values were 2–209 h, 35.28–234 h, and 0.98–2.13 h, respectively. In some circumstances alkaline slurries were observed to enhance the degradation rate when compared to those for neutral pH, for tylosin, the respective changes in DT50 values were from 3.52 to 35.28 h. Comparatively, the degradation of sulfamethoxazole was enhanced by acidic conditions compared to neutral (DT50 20.6–31.6 h). Tentative identification of unknown transformation products (TPs) was achieved for sulfamethoxazole and florfenicol for the first time in pig slurries. These results reveal the importance of considering slurry pH when assessing the degradation of antibiotic compounds, which has implications for the acidification of manures and the environmental risk assessment for veterinary medicines. Environmental relevance and significance : Given the significant effect of pig slurry pH on degradation rates, manure degradation studies need to be harmonised and standardized, taking into account the influence of pH. Graphical abstract: Image 1 Highlights: The effect of pig slurry pH on antibiotic degradation was compound specific. Abiotic and biotic processes contributed to this phenomenon. Differing route and rate of transformation products were observed. Manure degradation trials should employ multiple manures of differing properties.